Peran asam laktat pada nyeri otot rangka setelah latihan fisik - Dita Yuliastrid, (Ilmu Keolahragaan, 2012)
Abstract : Lactic acid is produced during intense levels of exercise when the oxygen demands of the muscle fibers increase beyond what the blood is capable of delivering. To produce the energy needed, the body begins another process, which works in the absence of oxygen. Lactic acida byproduct of this processlocks up your muscles, and because it is an acid it causes your muscles to experience that burning sensation. But lactic acid is completely washed out of the muscles within 30 to 60 minutes after finish the exercise.Since muscle soreness does not show up until 24 to 36 hours later. Over the 24 hours, the damaged muscle becomes swollen and sore. Chemical irritants are released from the damaged muscles and can irritate pain receptors. In addition to the injured fibers, there is increased blood flow from increased activity to the muscle, causing a swelling of the muscle tissues, which causes enough pressure to stimulate pain receptors. Instead of having free-moving muscle fibers the next morning, the fibers that are fatigued, have microscopic tears and are swollen. Key words : lactic acid, skeletal muscle soreness